Formulasi dan Uji Aktivitas Serum Spray Gel Minyak Adas (Feoniculum Vulgare Mill.) terhadap Bakteri Propionibacterium Acnes - Agistia, Nesa; ., Nofriyanti; Pratiwi, Erniza; Azizah, Mifza (LPPM Universitas Dharma Andalas, 2026)
Acne is a prevalent dermatological condition primarily caused by the bacterium Propionibacterium acnes. Antibiotics are used in acne therapy; however, increasing bacterial resistance has been reported in numerous studies. Fennel (Foeniculum vulgare Mill.) essential oil is known to exhibit antibacterial properties, mainly due to its active constituents, anethole and fenchone. This study aimed to develop a pharmaceutically stable serum spray gel formulation containing fennel essential oil and to evaluate its anti-acne activity. Fennel essential oil was formulated into serum spray gel preparations at concentrations of 10%, 15%, and 20%. The formulations were evaluated for organoleptic characteristics, pH, homogeneity, viscosity, flow behavior, adhesiveness, physical stability, spray pattern, and antibacterial activity.The results demonstrated that all serum spray gel formulations exhibited good physical stability, as indicated by acceptable organoleptic properties, homogeneity, pH values, viscosity, flow behavior, adhesiveness, stability, and spray patterns. One-way analysis of variance (ANOVA) revealed a statistically significant difference (p < 0.05) among the formulations in terms of antibacterial activity, as measured by the diameter of the inhibition zones. Post hoc Tukey analysis showed that the 10% fennel essential oil formulation exhibited the highest antibacterial activity, with an inhibition zone diameter of 23.6 mm, which was classified as strong antibacterial activity.